Study of "the upper Cabo Ladrillero beds" in the homonym locality, lower Miocene of the Austral basin, Tierra del fuego - Tudisca, E.P. (2012)
In the cliffs of the Ladrillero cape, situated on the Atlantic coast of the Isla Grande de Tierra del Fuego, the uppermost records of the Austral or Magallanes foreland basin infill crop out. This locality contains Lower Miocene deposits informally named "Cabo Ladrillero beds" and "Cabo San Pablo beds" being the "upper Cabo Ladrillero beds" analyzed in this paper. This locality is situated around ten kilometers to the north of the emerging orogenic front (Punta Gruesa locality) where four facies association have been defined from gravitationally-driven supra batial to prograding and shallowing upward deltaic wedges. Deformed and massive beds by liquefaction processes and resedimentation are connected with abundant clastic dykes and synsedimentary faults. The statistic study suggests they are associated tectonic activity related to a transtensive episode rather than tectonic quiescence sometimes suggested in previous works. We conclude that microfossils documented in the area and used as a tool to support a deep marine environment are situated in underlying stratigraphic intervals that form part of the Desdémona Formation and the "lower Cabo Ladrillero beds" cropping out to the south of the study area. Sedimentological evidence are not conclusive respect to the batimetry but absence of classical turbidites, hyperpycnal flows and abundant deformed and resedimented deposits are more compatible with deltaic deposits, with high detritus supply generating unstable slopes rather than deep marine depositional settings, suggesting a more complex depositional evolution than the foraminiferal-based framework dominant in the literature.